A transposição da aridez em Vidas Secas: do livro ao filme - Andrade, Maria Bevenuta Sales de (2011)
The process of adaptation allows the approximating of two distinct areas, literature and cinema, making it possible, thus, the verification of the exchange system existing between them. Regarding such statement, this work is a study on the novel Vidas secas (1938), by Graciliano Ramos, and its homonymous film adaptation (1963), directed by Nelson Pereira dos Santos, in which questions concerning their dialogs, as well as the specificities and peculiarities that make up each artistic language, shall be scrutinized. The goal here is to analyze how the transposition of the literary text barrenness to the film took place, verifying how each artistic expression managed to expose the barren aspects in each narrative, especially concerning its relational and spatial forms, and, from this common element, emphasize which dialogic relations are established between the texts. For doing so, Mikhail Bakhtin (1997; 1998; 1999; 2003), and his concept of dialogism, is one of the theoreticians that contributed the most to this investigation, mainly for having provided a wider range of possible relations between both medias, entitling, thus, a study apart from the idea of fidelity. In order to widen the basis, several theoreticians from related areas have been employed: from film studies, the area of adaptation has been considered, in names such as Brian McFarlane (1996), Robert Stam (1992; 2003; 2006; 2008) and Ismail Xavier (1983; 2001; 2003), as well as those who have directed the attention to image analysis, such as André Gaudreault e François Jost (2009) and Jacques Aumont (1995); from literature, studies from literary theory have been used, as Gérard Genette (1995; 2006; 2008), Claudia Barbieri (2009) and Antonio Candido (2006), and also criticism referring to Vidas secas, such as Rui Mourão (1971), Antonio Candido (1992), Luís Bueno (2006), Maria Izabel Brunacci (2008). After conducting the theoretical and critical readings and the analysis, a series of dialogs has been found, both in the relationships of denouncing and the demarcation of a national identity, as well as the using of specific components of each art to highlight the reality of individuals. Therefore, it has been concluded that novel and film come together both in themes as well as in the form of narrative approach.